Under pressure: The paradox of autonomy and social norms in drug education - Farrugia, Adrian (The International journal of drug policy, 2023)
Much contemporary youth drug education operates from the assumption that young people's decisions to use alcohol and other drugs often stem from a misunderstanding that youth consumption is so common as to constitute a ‘social norm’. Known as the ‘social norms’ approach, the stated aim of this form of drug education is to empower young people to avoid consumption by constituting it as uncommon and, therefore, abnormal. Taking the relationship between autonomy and norms as my primary concern, I examine key assumptions of the social norms approach through an analysis of a dataset of 23 ‘evidence-based’ drug education texts currently recommended for use in Australian secondary schools. Drawing on Rasmussen's (2011) analysis of autonomy as a ‘paradox’ in which young people are compelled to demonstrate their autonomy by submitting to external authority, I argue that drug education constitutes young people's (lack of) autonomy as the key cause of and solution to youth drug use through three strategies: (1) decision-making exercises that position consumption as the result of an inability to make the rational choice; (2) activities that equate drug consumption with succumbing to peer pressure and failing to demonstrate autonomy; and (3) deployment of population level data on youth drug use that constitutes it as atypical. Together these strategies suggest that while drug education often purports to empower young people to make empowered decisions, it operates as a broader social intervention that seeks to produce compliant rather than autonomous subjects.